2015
DOI: 10.1088/0004-637x/799/2/158
|View full text |Cite
|
Sign up to set email alerts
|

Dust Destruction Rates and Lifetimes in the Magellanic Clouds

Abstract: The nature, composition, abundance, and size distribution of dust in galaxies is determined by the rate at which it is created in the different stellar sources and destroyed by interstellar shocks. Because of their extensive wavelength coverage, proximity, and nearly face-on geometry, the Magellanic Clouds (MCs) provide a unique opportunity to study these processes in great detail. In this paper we use the complete sample of supernova remnants (SNRs) in the MCs to calculate the lifetime and destruction efficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 98 publications
8
90
0
Order By: Relevance
“…Most recent calculations show that in the local solar neighbourhood SNRs destroy more dust than is produced by SNe and asymptotic giant branch (AGB) stars combined (Bocchio et al 2014;Slavin et al 2015, and references therein). Similar conclusions were reached for the Magellanic Clouds (Temim et al 2015). This imbalance between the production and destruction rate also prevails in local and high-redshift galaxies; this suggests that dust may need to reconstitute by accretion in the dense phases of the interstellar medium (ISM; Dwek & Scalo 1980;Valiante et al 2011;Gall et al 2011a,b).…”
Section: Introductionsupporting
confidence: 54%
“…Most recent calculations show that in the local solar neighbourhood SNRs destroy more dust than is produced by SNe and asymptotic giant branch (AGB) stars combined (Bocchio et al 2014;Slavin et al 2015, and references therein). Similar conclusions were reached for the Magellanic Clouds (Temim et al 2015). This imbalance between the production and destruction rate also prevails in local and high-redshift galaxies; this suggests that dust may need to reconstitute by accretion in the dense phases of the interstellar medium (ISM; Dwek & Scalo 1980;Valiante et al 2011;Gall et al 2011a,b).…”
Section: Introductionsupporting
confidence: 54%
“…For example, it is possible that the efficiency of dust destruction depends on environment in a more complex manner than we have represented in our model. Furthermore, there might be a metallicity dependence to the efficiency of dust destruction (Yamasawa et al 2011). Temim et al (2015 found the dust destruction rate in the Large Magellanic cloud to be lower than in the Small Magellanic Cloud.…”
Section: Insights From Comparing Model Variantsmentioning
confidence: 99%
“…To match the observed dust mass function at z > 1, we might need a prescription for dust production and destruction that allows more variation with galaxy properties, therefore evolving with time. For example, dust production in the ejecta of SN may be higher at early times (Dwek et al 2014), or destruction rate varies with the ambient gas density and metallicity (Temim et al 2015).…”
Section: Dust Mass Functionmentioning
confidence: 99%